Lung arteriovenous fistula: Medical - surgical treatment. Analysis of our experience - Praderi, Luis A.; Muras, Olga; Torres, Jorge E. (Cirugía del Uruguay, 1979)
The analysis of national' case material comprises 14 cases we have given special consideration to indications and surgical procedures. The sole therapy of these lesions consists in surgery. Scope of indications is increasingly wider and directly connected with anatomical and clinical type of lesion. Stress is laid in Parker and Stallworth's conservatlve procedure which consists in an aneurysmectomy, which is indicated in multiple bilateral' non - marginal forms. We have successfully applied this method to N° 9 case in our series; the multiple or bilateral form compels the surgeon to be ultra conservative.